Impact of Reset Pulse Width on Gradual Conductance Programming in Al2O3/TiOx-Based RRAM - Hyeonseong Lim; Wonbo Shim; Tae-Hyeon Kim (Micromachines)
This work investigates the impact of reset pulse width on multilevel conductance programming in Al2O3/TiOx-based resistive random access memory. A 32 × 32 cross-point array of Ti (12 nm)/Pt (62 nm)/Al2O3 (3 nm)/TiOx (32 nm)/Ti (14 nm)/Pt (60 nm) devices (2.5 µm × 2.5 µm active area) was fabricated via e-beam evaporation, atomic layer deposition, and reactive sputtering. Following an initial forming step and a stabilization phase of five DC reset–set cycles, devices were programmed using an incremental step pulse programming (ISPP) scheme. Reset pulses of fixed amplitude were applied with widths of 100 µs, 10 µs, 1 µs, and 100 ns, and the programming sequence was terminated when the read current at 0.2 V exceeded a 45 µA target. At a 100 µs reset pulse width, most cycles exhibited abrupt current jumps that exceeded the target current, whereas at a 100 ns width, the programmed current increased gradually in all cycles, enabling precise conductance tuning. Cycle-to-cycle variation decreased by more than 50% as the reset pulse width was reduced, indicating more uniform filament disruption and regrowth. These findings demonstrate that controlling reset pulse width offers a straightforward route to reliable, linear multilevel operation in Al2O3/TiOx-based RRAM.